Two sequential PCR amplifications for detection of Schistosoma mansoni in stool samples with low parasite load - Espírito-Santo, Maria Cristina Carvalho do; Alvarado-Mora, Mónica Viviana; Pinto, Pedro Luiz Silva; Carrilho, Flair José; Pinho, João Renato Rebello; Gryschek, Ronaldo Cesar Borges (Revista do Instituto de Medicina Tropical de São Paulo, 2012)
Schistosomiasis constitutes a major public health problem, with an estimated 200 million individuals infected worldwide and 700 million people living in risk areas. In Brazil there are areas of high, medium and low endemicity. Studies have shown that in endemic areas with a low prevalence of Schistosoma infection the sensitivity of parasitological methods is clearly reduced. Consequently diagnosis is often impeded due to the presence of false-negative results. The aim of this study is to present the PCR reamplification (Re-PCR) protocol for the detection of Schistosoma mansoni in samples with low parasite load (with less than 100 eggs per gram (epg) of feces). Three methods were used for the lysis of the envelopes of the S. mansoni eggs and two techniques of DNA extraction were carried out. Extracted DNA was quantified, and the results suggested that the extraction technique, which mixed glass beads with a guanidine isothiocyanate/phenol/chloroform (GT) solution, produced good results. PCR reamplification was conducted and detection sensitivity was found to be five eggs per 500 mg of artificially marked feces. The results achieved using these methods suggest that they are potentially viable for the detection of Schistosoma infection with low parasite load.